Effect of Apolactoferrin on Experimental Pneumococcal Otitis Media - Schachern, Patricia A. (2010)
OBJECTIVE: To find the effect of apolactoferrin administration on the middle and inner ears after experimentally induced pneumococcal otitis media. DESIGN: Histopathologic and morphometric analysis of the middle and inner ears. SETTING: University of Minnesota, Minneapolis. SUBJECTS: Ten chinchillas. INTERVENTIONS: The middle ear cavities of chinchillas were inoculated bilaterally with type 2 wild-type Streptococcus pneumoniae. Twenty-four hours later, the ears of 5 of the animals were injected with phosphate-buffered saline (PBS) and the other 5 with human apolactoferrin. The animals were killed 24 hours after the last injection. Bacterial counts were made of the middle ear effusions, and the cochleae were processed for histologic analysis. The thickness of the round window membranes and bacterial and inflammatory cell infiltration of the round window membranes, and scala tympani and damage of the hair cells and stria vascularis were compared for these 2 groups of animals. MAIN OUTCOME MEASURES: Comparison of inflammatory and bacterial cells in the middle and inner ears, and damage to inner ear structures. RESULTS: Bacterial plate counts of middle ear effusions (P = .005) and the number of inflammatory cells in the round window membrane (P = .047) were significantly lower in the apolactoferrin group compared with the group treated with PBS. CONCLUSION: Further investigation of apolactoferrin as a nonantibiotic approach for the treatment of otitis media and its complications is needed to confirm its safety and efficacy.